2001
DOI: 10.1038/35057247
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for non-selective preservation of organic matter in sinking marine particles

Abstract: The sinking of particulate organic matter from ocean surface waters transports carbon to the ocean interior, where almost all is then recycled. The unrecycled fraction of this organic matter can become buried in ocean sediments, thus sequestering carbon and so influencing atmospheric carbon dioxide concentrations. The processes controlling the extensive biodegradation of sinking particles remain unclear, partly because of the difficulty in resolving the composition of the residual organic matter at depth with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
231
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(253 citation statements)
references
References 21 publications
9
231
1
4
Order By: Relevance
“…The data show a negative relation, with opal being enriched with increasing water depth, reflecting fast organic matter degradation and slow BSi dissolution during water column transit. It has been hypothesized by Lee et al (2000) and Hedges et al (2001) that mineral ballast (BSi, CaCO 3 , and terrigenous compounds) inhibit carbon mineralization before reaching the sediment surface. Then, the correlation of benthic Si release and O 2 uptake in the dataset could be a result of BSi protecting the cytoplasmic OM from decay, as proposed by Armstrong et al (2002) and Moriceau et al (2009) for sinking particles in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…The data show a negative relation, with opal being enriched with increasing water depth, reflecting fast organic matter degradation and slow BSi dissolution during water column transit. It has been hypothesized by Lee et al (2000) and Hedges et al (2001) that mineral ballast (BSi, CaCO 3 , and terrigenous compounds) inhibit carbon mineralization before reaching the sediment surface. Then, the correlation of benthic Si release and O 2 uptake in the dataset could be a result of BSi protecting the cytoplasmic OM from decay, as proposed by Armstrong et al (2002) and Moriceau et al (2009) for sinking particles in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatographic analyses have identified glucosamine and galactosamine in HMWDOM, but at concentrations of ≤ 2% HMWDOC (Aluwihare et al, 1997;. Similar inconsistencies have also been reported for plankton and sinking particulate organic matter (Hedges et al, 2001;.…”
Section: Introductionmentioning
confidence: 66%
“…It has been observed that silicate and calcium carbonate biominerals and aluminosilicates in marine environment play an important role in protecting organic carbons, such as amino acids and proteins, from hydrolytic enzymes throughout the water column and surface sediments, leading to their non-selective preservation (Hedges et al, 2001;Ingalls et al, 2003;Mayer, 1994a;Ransom et al, 1998;Tosca et al, 2010). Micropores and mesopores in soil minerals have a similar role in the preservation of soil organic carbon (SOC) (Knicker, 2004;Krull et al, 2003;Mayer, 1994b;Mayer et al, 2004).…”
Section: Inhibition On Biodegradationmentioning
confidence: 99%